IntAct: intra‐operative fluorescence angiography to prevent anastomotic leak in rectal cancer surgery: a randomized controlled trial. (8th June 2018) - Armstrong, G.; Croft, J.; Corrigan, N.; Brown, J. M.; Goh, V.; Quirke, P.; Hulme, C.; Tolan, D.; Kirby, A.; Cahill, R.; O'Connell, P. R.; Miskovic, D.; et al.
Abstract: Aim: Anastomotic leak (AL) is a major complication of rectal cancer surgery. Despite advances in surgical practice, the rates of AL have remained static, at around 10–15%. The aetiology of AL is multifactorial, but one of the most crucial risk factors, which is mostly under the control of the surgeon, is blood supply to the anastomosis. The MRC/NIHR IntAct study will determine whether assessment of anastomotic perfusion using a fluorescent dye (indocyanine green) and near‐infrared laparoscopy can minimize the rate of AL leak compared with conventional white‐light laparoscopy. Two mechanistic sub‐studies will explore the role of the rectal microbiome in AL and the predictive value of CT angiography/perfusion studies. Method: IntAct is a prospective, unblinded, parallel‐group, multicentre, European, randomized controlled trial comparing surgery with intra‐operative fluorescence angiography (IFA) against standard care (surgery with no IFA). The primary end‐point is rate of clinical AL at 90 days following surgery. Secondary end‐points include all AL (clinical and radiological), change in planned anastomosis, complications and re‐interventions, use of stoma, cost‐effectiveness of the intervention and quality of life. Patients should have a diagnosis of adenocarcinoma of the rectum suitable for potentially curative surgery by anterior resection. Over 3 years, 880 patients from 25 European centres will be recruited and followed up for 90 days. Discussion: IntAct will rigorously evaluate the use of IFA in rectal cancer surgery and explore the role of the microbiome in AL and the predictive value of preoperative CT angiography/perfusion scanning.